2020
DOI: 10.1371/journal.pone.0232822
|View full text |Cite
|
Sign up to set email alerts
|

SimSurvey: An R package for comparing the design and analysis of surveys by simulating spatially-correlated populations

Abstract: Populations often show complex spatial and temporal dynamics, creating challenges in designing and implementing effective surveys. Inappropriate sampling designs can potentially lead to both under-sampling (reducing precision) and over-sampling (through the extensive and potentially expensive sampling of correlated metrics). These issues can be difficult to identify and avoid in sample surveys of fish populations as they tend to be costly and comprised of multiple levels of sampling. Population estimates are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The effects of changing survey approaches on the provisioning of scientific advice can be examined using observation system simulation models (Regular et al. 2020). Research into new methods that can augment existing surveys is also needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of changing survey approaches on the provisioning of scientific advice can be examined using observation system simulation models (Regular et al. 2020). Research into new methods that can augment existing surveys is also needed.…”
Section: Resultsmentioning
confidence: 99%
“…Advancing research methods and scientific practices for evaluating existing scientific survey designs and the identification, evaluation, and integration of new survey approaches are primary steps (Gill et al 2020;Methratta et al 2020). The effects of changing survey approaches on the provisioning of scientific advice can be examined using observation system simulation models (Regular et al 2020). Research into new methods that can augment existing surveys is also needed.…”
Section: Theme 1: Support Regulatory Processesmentioning
confidence: 99%
“…They concluded that the third model was the only service model to have a positive ROI over 3 years. 2 It eliminates patient dissatisfaction as they do not need to worry about transportation and is economically beneficial.…”
Section: Sirmentioning
confidence: 99%
“…We believe that a specific protocol for choosing the sample facility can eliminate the possibility of selection bias. 2 Also, maintenance of the cold chain is integral for the potency of oxytocin, it would be of importance to mention if this facet was adhered to strictly because Uttar Pradesh is known for its frequent episodes of power cuts. Furthermore, it would be helpful if the authors could share the '28 essential birth practices' checklist, to allow better understanding of the coaching involved in training the birth attendants.…”
Section: Acknowledgementmentioning
confidence: 99%